Doktrin Kristologi: Apologetika Natur Keallahan, Kemanusiaan, dan Kemesiasan Yesus berdasarkan Markus 9:2-13 - Budiman, Sabda; Panggarra, Robi; Beriang, Senan (KAMASEAN: Jurnal Teologi Kristen, 2023)
Throughout the church's history, the debate on Christology has been an important and controversial topic. One is about the Divinity and humanity of Jesus, which has been a long debate in the history of Christianity. Jesus' divinity and humanity are essential because they relate to the foundation of the believer's faith. In addition to the debate about the Christology of Jesus among Christians, there is another debate among the Jews about the person of Jesus himself, namely that Jesus is not the Messiah. Although many biblical texts have been used to defend the issue of Christology, there are still other biblical texts that have not been studied as a basis for discussing the issue. The purpose of this study is to add primary biblical references to the apologetics of Christology. The biblical basis for examining the nature of Godliness and humanity and the Messiahship of Jesus is the Gospel of Mark 9:2-13. The method used is the exegesis method. This method is suitable for finding a clear meaning of the word to be analyzed. The result of this study is that the words Transfigured (metamorphoo) , Son (huios), and Man (anthropos) explain that Jesus is a true man and a true God and as Heir, that is, the anointed Messiah of God.